Perbedaan Latihan High Intensity Ground Walking Dan Latihan Static Bicycle Terhadap Kapasitas Latihan Pada Penderita PPOM - Setiawan Setiawan; Nur Basuki (Poltekkes Kemenkes Surakarta, 2016)
Abstract: High Intensity Ground Walking, Static Bicycle exercise, exercise capacity, the 6-minutes walking test, chronic obstructive pulmonary disease (COPD). This study aimed to compare the benefits between High Intensity Ground Walking exercise and Static Bicycle exercise on exercise capacity in patients with chronic obstructive pulmonary disease (COPD). This research is a quasi-experimental study design with two groups pre and post test design. The subjects were all patients COPD with moderate and severe degree in The Special hospital of Pulmonary dr. Ario Wirawan Salatiga, that meet the inclusion and exclusion criteria. Inclusion criteria: (1) the degree of moderate and severe COPD (2) Age 25 to 70 years, (3) Value of FEV1 less than 60% (4) There is a decrease in exercise tolerance with the results of the 6-minute test less than 300 meter (5) Willing to follow this research. Exclusion criteria: (1) Having a concomitant diseases such as heart, kidney failure, uncontrolled diabetes, severe hypertension (2) need an ambulation aid (3) Having musculoskeletal and neuromuscular disorders of the lower extremities. Do not follow the exercises more than 3 times. The data was collected directly by assessing the results of the six-minute walk test before and after the treatments. Data collected were analyzed using SPSS 11.5. The different test within groups measured with Wilcoxon test, and for between groups measured wirh Mann Whitney test. The significance level was set on 0.05. Results and Conclusion:(1)High Intensity Ground Walking exercises improve exercise capacity in patients with COPD (p = 0.005), (2) Static Bicycle training program improve exercise capacity of patients with COPD (p = 0.005), (3) There is no difference between High Intensity Ground Walking Exercise and Static Bicycle training in improving exercise capacity in patients with COPD (p = 0.970).